MATERNAL DEPRESSION AND NONVERBAL ATTUNEMENT - Vende-Kotova, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Nonverbal attunement is when mother attunes with emotional state of the child by changing her nonverbal behaviour (posture, facial expressions, movement rhythm, speed, etc.) instead of using verbal means of expression such as naming child's activity, verbal reflection or interpretation. Mother's difficulty to attune with a child is associated with high rates of the psychopathology in children (Allen, Fonagy, & Baterman, 2008). The research aimed to determine whether and what are the correlations between mother’s depression symptoms and to her ability nonverbally attune to her child. 30 mothers and their children participated in this part of the research by performed creative tasks. Maternal nonverbal attunement with a child was determined using the Nonverbal Attunement Scale (Vende & Čukurs, 2011). Mothers also filled in the Beck Depression Inventory (BDI II Beck Depression Inventory; Beck, Steer, & Brown, 1996). Research findings indicate that maternal depression symptoms are not correlated to maternal nonverbal attunement with a child, and that is inconsistent with existing research. There was additionally examined child's ability to attune nonverbally to the mother in relation with maternal depression symptoms. These results show that maternal depression symptoms are negatively correlated to child's ability to mirror the mother nonverbally.